Minimum Area of Apartment Units for Nuclear Family Based on Anthropometric Approach: English - Septia Faril Lukman; Joko Adianto (Department of Architecture Universitas Muhammadiyah Jakarta, 2026)
Jakarta faces pressure in providing housing in strategic locations due to soaring land prices. This study aims to formulate the design of the smallest feasible apartment unit that still meets minimum habitability standards for a family with two children, using an anthropometric-based. The research centers on the utilization of air rights above the Blok M Terminal, a public space that has remained underutilized. A quantitative method was employed through surveys of 28 families, gathering data on body dimensions, daily activity patterns, and household furniture sizes. Findings reveal that the minimum spatial requirement per individual reaches 7.95 m², with the total net unit size at 31.80 m². This figure falls below the SNI 03-1733-2004 standard (9 m²/person) but exceeds the Ministry of Public Works’ benchmark (7.2 m²/person). To enhance efficiency, several functions are consolidated, such as the integration of the living and dining areas or laundry and drying area.